2014
DOI: 10.1002/uog.14593
|View full text |Cite
|
Sign up to set email alerts
|

P30.21: Saline infusion sonography in women presenting with post‐menopausal bleeding: positive predictive value and patient experience

Abstract: Objectives: Endometrial pathologies are common ultrasound findings in group of peri and postmenopausal women and are an indication for further diagnostics including biopsy, curettage, hysteroscopy. This study assessed whether a new elastography application with quantification possibility can differentiate normal and abnormal endometrium and to be a helpful tool to establish further management. Methods: The study included a group of 47 patients with endometrial thickness more than 5 mm. Elastographic images of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Similarly studies by Yildizhan et al and Dwivedi et al in postmenopausal women showed abnormality in 72% and 60% patients, respectively. 9,10 The sensitivity, specificity, PPV, and NPV of SIS in the detection of intrauterine abnormality in the present study was 96.2%, 71.4%, 92.9%, and 83.3%, respectively, while Kazandi et al's study showed sensitivity and specificity of SIS being 97%, 60%, 81%, and 93%, respectively, which was similar to the results of the present study. 11 While Bingol et al and Erdem et al studies showed sensitivity of 89.6% and 97.7% and specificity of 77.3% and 82.4%, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly studies by Yildizhan et al and Dwivedi et al in postmenopausal women showed abnormality in 72% and 60% patients, respectively. 9,10 The sensitivity, specificity, PPV, and NPV of SIS in the detection of intrauterine abnormality in the present study was 96.2%, 71.4%, 92.9%, and 83.3%, respectively, while Kazandi et al's study showed sensitivity and specificity of SIS being 97%, 60%, 81%, and 93%, respectively, which was similar to the results of the present study. 11 While Bingol et al and Erdem et al studies showed sensitivity of 89.6% and 97.7% and specificity of 77.3% and 82.4%, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…In the Ma and Dwivedi study, SIS diagnosed normal endometrium in 40%, endometrial polyps in 45%, thickened endometrium in 7.5%, and inconclusive findings in 7.5% of patients. 9 The postmenopausal group in the Yildizhan study showed polyps in 32.0%, submucosal fibroids in 24.0%, intramural fibroids in 8.0%, hyperplasia in 8.0%, and normal report in 28.0% patients. 10 In this study, abnormal findings on SIS were found in 28 patients (82.4%) while the remaining 6 patients (17.6%) showed no abnormality (thin/scanty endometrium).…”
Section: Discussionmentioning
confidence: 91%